Japanization and the Chinese "Madman": Triangulating Takeuchi Yoshimi's philosophy of translation. Issue 1 (2nd January 2016) - Chan, Leo Tak-hung
ABSTRACT: The special nature of Sino-Japanese translation, with a history as long as that of vernacular translations of Greek and Latin, is worth exploring because it can throw new light on Eurocentric and universalist approaches to translation theorizing. The tradition of translating between China and Japan, disrupted and then reinvigorated by the "invasion of Europe" in the nineteenth century, is the subject of ruminations by Takeuchi Yoshimi (1910–77), a prominent twentieth-century Sinologist. Takeuchi triangulates the relationship between Japan, China and the West in a way that forces a deeper reconsideration of the notion of the "translational". The West (the Other) is a means through which identity can be constructed by Japan (the Self), but given Japan's long history of being shaped by/shaping the China imaginary, China is also Japan's Other. Takeuchi's prime interest is in Japan projecting its own identity onto China (via Lu Xun). In the present article, Takeuchi's two translations of Lu Xun's "The Diary of a Madman" in 1956 and 1976 are compared with those by Inoue (1932), Oda and Tanaka (1953) and Komada (1974) to understand how Takeuchi's advocacy of a realignment with China (and Asia) constitutes an attempt to reconstrue a Japanese identity that would refute the West's monistic view of civilization.